2016
DOI: 10.2147/ott.s95020
|View full text |Cite
|
Sign up to set email alerts
|

A case of acanthosis nigricans as a paraneoplastic syndrome with squamous cell lung cancer

Abstract: A 55-year-old man presented with oral mucosal ulcers, blackening of both hands, and hyperpigmentation on axillary, anal, and inguinal regions for the last 3 months, which were all progressive. The patient was referred to the oncology department with the diagnosis of acanthosis nigricans for investigation of an underlying malignancy. He was a smoker. A computed tomography scan of thorax revealed enlarged mediastinal lymphadenopathies and a lesion on the left upper lobe. Fine-needle aspiration biopsy of the medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 17 publications
(23 reference statements)
0
0
0
Order By: Relevance
“…Recent reviews have found that it was difficult to avoid local infections even if the dosage was controlled within 15 mg/day. In patients with obesity, glaucoma, depression, and hypertension, the dose of 5-10 mg/ day may also cause varying degrees of adverse effects (Karakas et al, 2016). Although the efficacy of thalidomide in the treatment of RAU has been increasingly recognized, some patients may still experience symptoms such as dizziness, constipation, and rash that are difficult to avoid.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews have found that it was difficult to avoid local infections even if the dosage was controlled within 15 mg/day. In patients with obesity, glaucoma, depression, and hypertension, the dose of 5-10 mg/ day may also cause varying degrees of adverse effects (Karakas et al, 2016). Although the efficacy of thalidomide in the treatment of RAU has been increasingly recognized, some patients may still experience symptoms such as dizziness, constipation, and rash that are difficult to avoid.…”
Section: Introductionmentioning
confidence: 99%